Arsenic hypertolerance in the protist Euglena mutabilis is mediated by specific transporters and functional integrity maintenance mechanisms. (28th April 2014) - Halter, David; Andres, Jérémy; Plewniak, Frédéric; Poulain, Julie; Da Silva, Corinne; Arsène‐Ploetze, Florence; Bertin, Philippe N.
Summary Arsenic is a toxic metalloid known to cause multiple and severe cellular damages, including lipid peroxidation, protein misfolding, mutagenesis and double and single‐stranded DNA breaks. Thus, exposure to this compound is lethal for most organisms but some species such as the photosynthetic protist Euglena mutabilis are able to cope with very high concentrations of this metalloid. Our comparative transcriptomic approaches performed on both an arsenic hypertolerant protist, i.e. E. mutabilis, and a more sensitive one, i.e. E. gracilis, revealed multiple mechanisms involved in arsenic tolerance. Indeed, E. mutabilis prevents efficiently the accumulation of arsenic in the cell through the expression of several transporters. More surprisingly, this protist induced the expression of active DNA reparation and protein turnover mechanisms, which allow E. mutabilis to maintain functional integrity of the cell under challenging conditions. Our observations suggest that this protist has acquired specific functions regarding arsenic and has developed an original metabolism to cope with acid mine drainages‐related stresses.